INDEXING PROBLEMS OF SCIENTIFIC PAPERS - Popovich, Inna A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article presents thoughts of practicing bibliographer about indexing of scientific articles in university library, there were analyzed the most common mistakes of UDC identifiers which are found in scientific periodicals.